2011
DOI: 10.1074/jbc.m111.268235
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Primer-induced Conformational Dynamics of HIV-1 Reverse Transcriptase on Polymerase Translocation and Inhibition

Abstract: The rapid emergence and the prevalence of resistance mutations in HIV-1 reverse transcriptase (RT) underscore the need to identify RT inhibitors with novel binding modes and mechanisms of inhibition. Recently, two structurally distinct inhibitors, phosphonoformic acid (foscarnet) and INDOPY-1 were shown to disrupt the translocational equilibrium of RT during polymerization through trapping of the enzyme in the pre-and the post-translocation states, respectively. Here, we show that foscarnet and INDOPY-1 additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Thus, assays can be developed to screen for novel translocation inhibitors. In this context it is important to note that both PFA and INDOPY-1 were shown to be ineffective in affecting the translocational equilibrium on RNA-primed reactions (Auger et al 2011 ). RT is able to fl ip between different conformations such as polymerase competent and RNase competent.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, assays can be developed to screen for novel translocation inhibitors. In this context it is important to note that both PFA and INDOPY-1 were shown to be ineffective in affecting the translocational equilibrium on RNA-primed reactions (Auger et al 2011 ). RT is able to fl ip between different conformations such as polymerase competent and RNase competent.…”
Section: Resultsmentioning
confidence: 99%
“…Like the natural dNTP substrate, INDOPY-1 can form a stable complex with HIV-1 RT and its primer⅐template substrate (6,8,45). These complexes are resistant to challenges with an enzyme trap, such as heparin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the INDOPY-1 analog 1-(4-nitrophenyl)-2-oxo-2,5-dihydro-1H-pyrido[3,2-b]indole-3-carbonitrile (VRX329747) ( Figure 13 ) selected HIV-1 RT mutated at the amino acid residues M41L, A62V, S68N, G112S, V118I, and M184V, which are all located around the incoming nucleotide-binding site [ 112 ]. Further, binding and biochemical studies revealed that (i) the M184V mutation reduces the affinity to INDOPY-1, while the Y115F mutation facilitates the dNTP binding, and their combined effects enhance the ability of the enzyme to discriminate against the inhibitor [ 113 ]; (ii) RT complexed with INDOPY-1 is trapped in the posttranslocational state [ 113 ]; (iii) the INDOPY-1 has preference with respect to substrate primer identity since its binding to RT is higher on a DNA:DNA versus a RNA:DNA primer:template [ 114 ]; (iv) when assayed by steady-state kinetic analysis with homopolymeric template primers, INDOPY-1 inhibits RT-catalyzed DNA polymerization with a competitive [ 111 ] or mixed-type [ 112 ] mode with respect to dNTPs. Overall, these observations suggest that the binding site of the indolopyridones and nucleotide substrates can at least partially overlap and they are therefore proposed as Nucleotide competing RT inhibitors (NcRTIs).…”
Section: Nucleotide Competing Rt Inhibitorsmentioning
confidence: 99%